Smart Irrigation and Monitoring System for Pot Plant - GAN, YAW KIAT; ABDULLAH, MOHAMMAD FAIZ LIEW (Evolution in Electrical and Electronic Engineering, 2023)
In light of the rapid advancements in modern technologies, people who are busy with work schedules sometimes result in neglecting the needs of their potted plants, such as watering and fertilizing. The main goal of this project is to develop a Smart Irrigation and Monitoring System that minimizes the effort to manage plants amidst busy schedules. This system enables users to monitor their plants’ health and make informed decisions regarding fertilization when nutrient deficiencies are detected. The project utilizes an Arduino Uno microcontroller to manage various sensors, including humidity, ultrasonic, and pH value sensors. An ESP-8266 Wi-Fi module is integrated into the system to provide Wi-Fi connectivity to the Arduino Uno, allowing it to connect to Wi-Fi networks and interface with the Blynk application, serving as the Internet of Things (IoT) platform. The implemented system automates irrigation, ensures an optimal water supply, and enables remote plant monitoring. Users receive warning notifications for pH value deviations based on the monitoring data, and the Blynk application facilitates convenient fertilization of plants. The system acts as an irrigation system while also providing real-time plant data monitoring for users.